Pengaruh Gaya Kepemimpinan Dan Budaya Organisasi Terhadap Kinerja Karyawan Pada PT Bisma Narendra Di Cibitung Kabupaten Bekasi - Shohibatul Azizah; Nurul Ilham (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Leadership style is defined as the attitude or way a leader manages his organization. Organizational culture is defined as the norms that operate in an organization. Employee performance can be interpreted as an employee's contribution to the company. The purpose of this research is to determine the influence of leadership style and organizational culture on employee performance at PT Bisma Narendra in Cibitung, Bekasi Regency. The method used is quantitative. The sampling technique used saturated sampling, namely 84 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that leadership style has a significant effect on employee performance with a coefficient of determination value of 37.4% and the hypothesis test obtained tcount > ttable or (7.005 > 1.989). Organizational culture has a significant effect on employee performance with a coefficient of determination value of 51.5% and hypothesis testing obtained tcount > t table or (9.329 > 1.989). Leadership style and organizational culture simultaneously have a significant effect on employee performance with the regression equation Y = 7.979 + 0.291X1 + 0.507X2. The coefficient of determination value is 56.9% while the remaining 43.1% is influenced by other factors. Hypothesis testing obtained a value of Fcount > Ftable or (53.469 > 2.720).